Le corps du diable entre théologie et sciences dans les textes contre la démonolâtrie aux XVe et XVIe siècles - Alfredo Perifano (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
The affirmation of the possibility for demons to assume a body was not a minor argument of the conceptual apparatus deployed between the late fifteenth century and the first three decades of the sixteenth in order to affirm the need for inquisitorial intervention and for a specific inquisitorial jurisdiction in the pursuit of this new form of heresy: demonolatry. Inquisitors intended, inter alia, to establish beyond doubt the reality of the nocturnal meetings which witches attended by moving through the air on animals or objects in order to perform blasphemous acts, which were apostatical by nature. Among them, there were orgies during which participants mated not only with each other, but also with demons. For demons to be at the origin of these two phenomena – that is to say witches / wizards flying through the air and the mating of humans and demons – the theological, philosophical as well as physical possibility to perform such acts had to be demonstrated. This article will examine some aspects of the relationship between theology, philosophy and physics in the discourses developed by inquisitors and demonologists between the late fifteenth and the sixteenth century in order to affirm the reality of the Sabbath.